The Impact of Self-Directed Learning Model with Articulate Storyline 3 on Vocational Students’ Motivation and Physics Achievement. - Tri Choirul Nur Amalia; Subiki Subiki; Firdha Kusuma Ayu Anggraeni (FKIP, Universitas Palangka Raya, 2025)
This research investigated how using Articulate Storyline 3 within a Self-Directed Learning (SDL) model affected vocational students' motivation and physics learning achievements. The study employed a true experimental design, specifically a Post-test Only Control Group Design and was carried out at SMK Negeri 2 Jember. Sample determination is done by conducting a homogeneity test, then randomly selected for the control class and the experimental class through a lottery. Data was collected using observation, interview, questionnaire, test and documentation methods. The data analysis technique used was normality test and T test with the help of IBM SPSS 25 software. Questionnaire results indicated that students in the experimental group, who used the Self-Directed Learning model with Articulate Storyline 3, showed higher average learning motivation compared to the control group. The results of data analysis of student learning motivation with the Independent Sample T-test test obtained a significance value of 0.010 ≤ 0.05, which means H0 is rejected and Ha is accepted. The post-test results revealed that students in the experimental group, who learned physics using the Self-Directed Learning model with Articulate Storyline 3, achieved higher average scores than those in the control group. The results of data analysis of student physics learning outcomes tested with the Mann-Whitney U-test get a significance value of 0.004 ≤ 0.05 which means H0 is rejected and Ha is accepted. So it can be concluded that there is a significant effect of the application of the SDL model accompanied by Articulate Storyline 3 media on student motivation and physics learning outcomes.